Blogs and e-Portfolios: can they support reflection, evidencing and dialogue in teacher training? - Simon Cotterill (Association for Learning Development in Higher Education (ALDinHE), 2010)
A blog with explicit support for structured skills/competencies and community publishing was integrated within an e-Portfolio and evaluated with three successive cohorts of PGCE secondary students at Newcastle University in order to support reflections on practice, weekly lesson evaluations, and to evidence Teaching Quality Standards (TQS). The technologies were initially piloted with a single subject (English with Drama) in 2007/8, with roll out to all thirteen PGCE programmes in 2008/9 (156 students and seven tutors). Focus groups and questionnaires were used to investigate students' perceptions of using the blog to support both reflection and evidencing, to identify factors relating to engagement, and to explore informal use of external social networking with course-mates. Tutors' views were also captured. Students accessed the portfolio an average of sixty three times each (the range being from 4 to 254) and uploaded a total of 1,785 files over a ten month period in 2008/9. Students made an average of 27 blog entries each (36% published to a community). Analysis of questionnaire data (37% response rate) indicated that students liked the approach of linking one item of evidence to multiple TQS and feeling 'in touch' whilst on placement. Students (89%) used external social networking sites (47% of students used them for course-related purposes). The main barrier to engagement with the e-Portfolio was the perceived lack of time on a busy course. This study informs debate on the level of structure required in e-Portfolios/blogs for vocational subjects and factors relating to engagement and concurrent use of formal/institutional and informal social networking sites.